2006
DOI: 10.1007/s10562-006-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Methane Transformation in Presence of Carbon Dioxide on Activated Carbon Supported Nickel–calcium Catalysts

Abstract: The objective of the present work was to study the catalytic reformation of methane in presence of carbon dioxide on activated carbon-supported nickel and calcium catalysts. Results are very promising ones because they suggests that it is possible to transform methane on these catalysts by using mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
2
24
1
Order By: Relevance
“…This is a deactivation of 90% and 70% relative to initial activities for Ni/AC and Ni-Ca/AC, respectively. In a previous work [10], we showed that catalytic activity of Ca/AC is negligible [10]. Therefore the present results suggest that calcium, in the form of CaO or CaCO 3 [10], would play a promoter role in the present bimetallic system, as has been earlier reported [3,6].…”
Section: Methane Conversion and Xps Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…This is a deactivation of 90% and 70% relative to initial activities for Ni/AC and Ni-Ca/AC, respectively. In a previous work [10], we showed that catalytic activity of Ca/AC is negligible [10]. Therefore the present results suggest that calcium, in the form of CaO or CaCO 3 [10], would play a promoter role in the present bimetallic system, as has been earlier reported [3,6].…”
Section: Methane Conversion and Xps Analysissupporting
confidence: 81%
“…(2) that in comparison to the crude catalyst the binding energy of nickel in Ni-Ca/AC decreased about 2 eV (from 855.8 eV to 853.9 eV) after He pre-treatment. By contrast, we showed [10] that in absence of calcium, the binding energy of Ni +2 , for Ni/AC, only decreased in about 0.9eV after He pre-treatment. The role of electron donors of CaO and CaCO 3 is well-known [15] and the present result suggest that calcium phases would induce an easier reduction of Ni +2 to lower oxidation states, probably by its interaction with carbon atoms from support [8].…”
Section: Methane Conversion and Xps Analysiscontrasting
confidence: 66%
See 3 more Smart Citations